Innovations in Analytical Platforms: Bridging Data Lakes and Al for Competitive Advantage - Rahul Ranjan (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The use of AI powered analytical tools combined with data lakes is changing the way data is stored, managed, and decisions are made. Nonetheless, issues of data quality, scalability, security, and the interoperability of different systems poses a challenge to effective implementation. Insufficient governance of data results in inaccurate insights, biased AI models, and inefficiencies in operations. This research focuses on addressing these gaps using scalable cloud-based structural solutions, real-time processing systems, and ethical AI governance. This research captures the call for standardized data cleansing, enhanced security protocols, and AI driven optimization using secondary data and thematic analysis. Results indicate that business intelligent systems will perform better and gain a sustainable competitive edge if these hindrances are removed. The study puts forward the ethical standards for compliance, non-discrimination, and innovation in AI powered data analytics and its results.